How do senior English teachers experience Global Englishes in language teaching? Narratives from within - Andri Jamaul Rifiyani; Ehsan Namaziandost; M. Faruq Ubaidillah; Budianto Langgeng (Studies in English Language and Education, 2025)
Extensive research on Global Englishes (GE) experiences has been investigated in response to the calls for using English as a global language and multicultural communication tool. However, previous studies were entirely concerned with higher education and language course teachers. Thus, to fill this lacuna, this current research dispensed the experiences of five senior English teachers dealing with GE in Islamic boarding school settings in Indonesia using a narrative inquiry. The five participants in this study were selected purposefully based on their teaching experience of more than 20 years. The data were gathered using individual in-depth interviews and analysed following Braun and Clarkes thematic analysis procedure. Results revealed that most participating teachers were unaware of the GE variations. Their inadequate knowledge of GE was seen in how they perceived issues of native-speaker ideology, the use of L1, the inclusion of Western culture, and the use of English textbooks in their classes. The studys findings suggest that raising GE awareness of English teachers is essential since the paradigm shift of English as a global language has received considerable and critical attention in academia. In addition, the findings demand GE awareness to be included in the secondary school English curriculum. Finally, the use of narrative inquiry in this study is also promising in revealing teachers lived experiences personally and professionally.